Sticky faith : everyday ideas to build lasting faith in your kids - Powell, Kara Eckmann, 1970-; Clark, Chap, 1954- (Grand Rapids, Mich. : Zondervan, 2011)
Research shows that almost half of graduating high school seniors struggle deeply with their faith. Recognizing the ramifications of that statistic, the Fuller Youth Institute (FYI) conducted the 'College Transition Project' in an effort to identify the relationships and best practices that can set young people on a trajectory of lifelong faith and service. Based on FYI findings, this guide presents both a compelling rationale and a powerful strategy to show parents how to actively encourage their children's spiritual growth so that it will stick to them into adulthood and empower them to develop a living, lasting faith. --from publisher description.
The not-so-sticky-faith reality -- The sticky Gospel -- Sticky identity -- Sticky faith conversations -- A sticky web of relationships -- Sticky justice -- A sticky bridge out of home -- The ups and downs of the sticky faith journey -- Appendix 1. The College Transition Project research overview -- Appendix 2. the HURT project research overview.
Includes bibliographical references (pages 213-222).
Keywords: Christian teenagers -- Religious life; Parenting -- Religious aspects -- Christianity; Child rearing -- Religious aspects -- Christianity; Christian education -- Home training; Parent and teenager -- Religious aspects -- Christianity